The cancellation heuristic in intertemporal choice shifts people’s time preferences - Sengupta, Arjun; Savani, Krishna (Scientific reports, 2022)
Building on past research in risky decision making, the present research investigated whether the cancellation heuristic is evident in intertemporal choice. Specifically, the cancellation heuristic posits that whenever choice options are partitioned into multiple components, people ignore seemingly identical components and compare the non-identical components. We nudged people to employ the cancellation heuristic by partitioning both the smaller earlier reward and the larger later reward into a seemingly identical component and a non-identical component. Given diminishing marginal utility, we hypothesized that people would perceive an identical difference between the smaller earlier reward and the larger later reward as being subjectively greater when both amounts are smaller in magnitude, thereby increasing the relative attractiveness of the larger later reward in the partition condition. We conducted four studies, including two incentive-compatible lab experiments, one incentive-compatible lab-in-the-field experiment, and one survey study using choices among both gains and losses. We consistently found that this choice architecture intervention significantly increased people’s likelihood of choosing the larger later reward. Furthermore, we provide evidence of the underlying mechanism-people’s intertemporal decisions shifted to a greater extent in the cancellation condition, particularly if their marginal utility diminished faster. The findings indicate that two features of human psychology-diminishing marginal utility and the cancellation heuristic-can be simultaneously utilized to nudge people to make decisions that would be better for them in the long run.
Gesehen am 18.05.2022